New trends in the use of medicinal plants by Algerian diabetic patients, considerations of herb-drug interactions. (28th June 2021) - Chelghoum, Mustapha; Khitri, Walid; Bouzid, Samia; Lakermi, AbdelRahim
Abstract: Ethnopharmacological relevance: Diabetes mellitus is a metabolic disorder, with a large prevalence in low- and middle-income countries. Numerous studies highlighted the use of medicinal plants for diabetes in Algeria. This use is influenced by cultural considerations. The industrialization of the country leads to the transformation of the trend of the utilization of plants, and the increase of polymedication. In this context, there is no information about the profile of diabetic patients using plants and the potential of herb-drug interactions. Aim of the study: The objective was to evaluate the use of plants by diabetic patients and to search the drug interactions with the most cited species. Materials and methods: Descriptive and comparative studies were carried out among diabetic patients and traditional healers, in the west of Algeria, to inventory the plants used in diabetes. Bivariate and multivariate analysis by logistic regression were performed to evaluate the associated factors with the use, to determine the profile of users. Bibliometric research in PubMed, Google Scholar, Cochrane Library and ClinicalTirals was conducted to look for herb-drug interactions. Results: Results show a decrease in the use of medicinal plants by diabetic patients, in comparison of previous findings, some of which have not been cited by traditional healers. The patients under oral anti-diabetic agents (ODA) have twice the risk to use plants in concomitant with drugs. Olea europea leaves and Trigonella feanum greacum seeds were the most cited herbals. Metformin was the most used drug. Several clinical trials revealed that the anti-diabetic plants had a synergistic effect with ODA, which can increase the hypoglycemia of diabetics. Non-important adverse reactions were noted. Conclusions: New trends of the use of medicinal plants by diabetic patients were noted, this is due to the diversification of information sources. Patients under ODA must be educated about the use and the risk of herb-drug interactions. Graphical abstract: Image 1 Highlights: The prevalence of medicinal plants used by diabetic patients is in decrease. Patients on oral anti-diabetic agents are twice susceptible using medicinal plants. The profile of the use and users of medicinal plants is in change because of the different sources of information. Anti-diabetic plants can increase hypoglycemia episodes of oral anti-diabetic agents.